Synthesis, characterization and multifunctional properties of plasmonic Ag–TiO2 nanocomposites. (26th July 2016) - Prakash, Jai; Kumar, Promod; Harris, R A; Swart, Chantel; Neethling, J H; van Vuuren, A Janse; Swart, H C
Abstract: We report on the synthesis of multifunctional Ag–TiO2 nanocomposites and their optical, physio-chemical, surface enhanced Raman scattering (SERS) and antibacterial properties. A series of Ag–TiO2 nanocomposites were synthesized by sol–gel technique and characterized by x-ray diffraction, scanning and transmission electron microscopy, energy-dispersed x-ray analysis, photoluminescence, UV–vis, x-ray photoelectron and Raman spectroscopy and Brunauer–Emmett–Teller method. The Ag nanoparticles (NPs) (7–20 nm) were found to be uniformly distributed around and strongly attached to TiO2 NPs. The novel optical responses of the nanocomposites are due to the strong electric field from the localized surface plasmon (LSP) excitation of the Ag NPs and decreased recombination of photo-induced electrons and holes at Ag–TiO2 interface providing potential materials for photocatalysis. The nanocomposites show enhancement in the SERS signals of methyl orange (MO) molecules with increasing Ag content attributed to the long-range electromagnetic enhancement from the excited LSP of the Ag NPs. To further understand the SERS activity, molecular mechanics and molecular dynamics simulations were used to study the geometries and SERS enhancement of MO adsorbed onto Ag–TiO2 respectively. Simulation results indicate that number of ligands (MO) that adsorb onto the Ag NPs as well as binding energy per ligand increases with increasing NP density and molecule-to-surface orientation is mainly flat resulting in strong bond strength between MO and Ag NP surface and enhanced SERS signals. The antimicrobial activity of the Ag–TiO2 nanocomposites was tested against the bacterium Staphylococcus aureus and enhanced antibacterial effect was observed with increasing Ag content explained by contact killing action mechanism. These results foresee promising applications of the plasmonic metal−semiconductor based nano-biocomposites for both chemical and biological samples.